MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKN) MELALUI METODE KOPERATIF ROTATING TRIO EXCHANGE (RTE) PADA SISWA KELAS IV DI SD NEGERI 70 KOTA TERNATE - Tawari, Iswan E (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
Improving Civic Education (Pkn) Learning Outcomes Through Cooperative MethodsRotating Trio Exchange (Rte)In Grade IV Students at State Elementary School 70, Ternate City, Ternate Institute of Science and Education (Isdik) Kie Raha North Maluku.This study aims to improve the learning outcomes of Civic Education (PKn) of fourth grade students of SD Negeri 70 Ternate City through the application of learning models.Rotating Trio Exchange (RTE). The problem of low interest and learning outcomes in Civics is caused by less innovative and monotonous learning methods. This Classroom Action Research (CAR) was conducted in two cycles, with 20 fourth-grade students of Gita State Elementary School as subjects in the 2025/2026 academic year.The results of the study showed a significant increase in student activity and learning outcomes. In Cycle I, student activity was in the "Sufficient" category (65%) and teacher activity was "Good" (72%). The average value of student learning outcomes was 68 with a classical completion of 60%, which had not yet reached the 80% success indicator. Based on the reflection of Cycle I, corrective actions were carried out in Cycle II. As a result, student activity increased to "Very Good" (88%) and teacher activity also reached "Very Good" (90%). This improvement had a positive impact on learning outcomes, with the average class value increasing to 82 and classical completion reaching 95%, which had exceeded the success indicator.